The Effect of Zigzag Dribbling Exercise on the Results of Dribbling Agility - Juan Sugesti Veron; Meirizal Usra; Ahmad Richard Victorian (Universitas Sriwijaya, 2023)
This study aims to determine the effect of zigzag dribbling training on dribbling agility in athletes at the Ogan Ilir 32 football school. The method used in this study was a quasi-experimental method. The research design used was one group pretest post-test design. Sampling using total population sampling technique with a total sample of thirty people. The research instrument was that all samples conducted a soccer dribbling agility test. The results of data processing and analysis using paired sample test, that zigzag dribbling exercises affect the results of soccer dribbling agility. This can be seen from the results of data analysis through the calculation of the ttest formula with the criteria tcount greater than t table (14.28˃1.70) with a confidence level of 0.95 and the number of samples (N = 30), the proposed hypothesis is accepted. The zigzag dribbling exercise really influences the results of soccer dribbling agility. Based on the results of the study, the zigzag dribbling exercise had a significant effect on the results of soccer dribbling agility in athletes at the Ogan Ilir 32 football school.